Marketing Intelligence dalam Menumbuhkan Jiwa Entrepreneur pada Generasi Milenial - Abdul Waris; Wahyu Setiyorini; Chodidjah Chodidjah (Jurnal Manajemen dan Kewirausahaan, 2020)
Indonesia is currently coming into a demographic dividend era occuring due to changes in the age structure of its population because the proportion of productive age is above 2/3 of the total population and around 50.36% of the population of productive age are basically millennial generation. This is an opportunity that must be utilized as well as possible by maximizing the capabilities of the current millennial generations which have open, free, critical, and courageous mindset as the essential things in entrepreneurship. The aim of this research is to find out the effect of marketing intelligence in growing the entrepreneurial spirit in millennial generations by using quantitative approaches and descriptive    analysis method. The results show that: 1) marketing intelligence activities performed by millennial generation can help growing the entrepreneurial spirit; and 2) marketing research has the dominant influence of the growing entrepreneurial spirit of the millennial generation in marketing intelligence activities. This marketing intelligence activity does not have to be done in a group, but it can be done independently or alone. https://doi.org/10.26905/jmdk.v8i1.4245